SEKOLAH PENCETAK WIRAUSAHA DALAM PERSPEKTIF ESD DI SMK BINA UTAMA KENDAL - Budiati, Idha; Febrihastatiwi, Dinda; Ajibudiarta, Riska; Roshayanti, Fenny (UNIB Press, 2024)
The high unemployment of vocational school graduates is an urgent problem that requires concrete solutions. The Directorate of Vocational Development in collaboration with SEAMEO developed the Entrepreneurial Printing School program to foster the entrepreneurial spirit of students to be able to build an independent and sustainable business. This study aims to explore the implementation of the ESD-based SPW program at SMK Bina Utama Kendal using a qualitative descriptive approach. Data was collected through observations, questionnaires, and interviews with students, teachers, and SPW managers. The results of the study show that in the environmental aspect, 60% of students reduce plastic waste through recycling, although waste management still needs to be improved. In the economic aspect, 85% of students felt that SPW training improved their skills in managing sustainable businesses. On the social aspect, 64% of students felt the positive impact of the program, although local community involvement needs to be strengthened. So that the ESD-based SPW program is effective in helping students become independent and sustainable entrepreneurs and can become a model for entrepreneurship education in other vocational schools.